High Entropy Alloys for Energy Conversion and Storage: A Review of Grain Boundary Wetting Phenomena - Straumal, Boris; Korneva, Anna; Kuzmin, Alexei; Klinger, Leonid; Lopez, Gabriel A.; Vershinin, Nikolai; Straumal, Alexander; Gornakova, Alena (MDPI, 2022)
The multicomponent alloys with nearly equal concentration of components, also known as high entropy alloys (HEAs), were first proposed 22 years ago. The HEAs quickly became very important in materials science due to their unique properties. Nowadays, the HEAs are frequently used in energy conversion and storage applications. HEAs can consist of five, six or more components. Plasma cladding permits coating of the large surfaces of cheap substrates with (often expensive) HEAs and to enlarge, in such a way, their application area. The large-area coatings deposited by plasma cladding possess multiple advantages such as low thermal distortion, very high energy density, as well as low dilution of the substrate material. Plasma cladding ensures good metallurgical bonding between coating and substrate. The costs of operation and equipment are also very attractive. During plasma cladding, the mixed powders are blown by carrier gas into a plasma torch or are positioned on a substrate. This powder mixture is then melted in or under the plasma torch. The plasma torch, in turn, sequentially scans the substrate. After finalizing the crystallization process, the solid polycrystal appears which contains few residual melts. This remaining melt can completely or incompletely wet the grain boundaries (GBs) in solid phase of the polycrystal. These completely or incompletely wetted GBs can strongly influence the microstructure of HEA coatings and their morphology. In this review we analyze the GB wetting HEAs containing one phase in HEAs with two, three and more phases, as well as in HEAs reinforced with particles of carbides, nitrides, borides, or oxides. We also analyze the microstructure of the rather thick coatings after plasma cladding after additional laser remelting and observe how GB wetting changes over their thickness.--//-- Published under the CC BY 4.0 licence.
This research was funded by the Russian Ministry of Science and Higher Education (contract no. 075-15-2021-945 grant no. 13.2251.21.0013). Support from the University of the Basque Country (project GIU19/019) and from the Basque Government (project IT1714-22) is also acknowledged.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; plasma cladding; coatings; wetting; phase transitions; high-entropy alloys; phase diagrams; grain boundary